Synthesis of high-temperature superconducting yttrium-barium cuprate single crystals and study of their properties - Bakuntseva, M.V.; Gorbik, P.P.; Dubrovin, I.V.; Kashin, G.N.; Laguta, I.V.; Nastasienko, A.I. (Поверхность, 2002)
The method of synthesis of stack-plated single crystals of YBa₂Cu₃O₆₊δ high-temperature superconductor has been improved. The method is based on combination of the processes of mass-nucleation and directional crystallization from the solution-melt by Czochralski. The single crystals with the natural cuts and plate habitus of 8 mm in length have been grown. Diffusion of silver from thin films (10-20 nm) into the YBa₂Cu₃O₆₊δ single crystals has been studied in the temperature range 373-773K with the use of Auger electron spectroscopy. Diffusion activation energy and pre-exponential factor have been determined. The mechanism with participation of oxygen vacancies has been suggested as a principal diffusion mechanism.